Procurement strategy for fresh vegetable produces to mitigate food waste in the retail sector - Mairinda Lestari; Fauzan Romadlon; Isnaini Nurisusilawati (Center for Science and Technology, IAIN Surakarta, 2024)
Food waste is critical issue in developing countries, including Indonesia, affecting both the retail and consumers. In the case of vegetables, food waste frequently arises due to their short shelf life, spoilage, and physical damage. Additionally, the instability of vegetable prices creates challenges for consumers in meeting their needs. In sufficiency in the vegetable supply chain exacerbate the problem leading to leftovers and waste. This research aims to explore the causes of vegetable food and propose effective procurement strategies to mitigate it. A quantitative research approach was employed, with data collected through structured interviews involving 127 vegetable traders. The analysis utilized ANOVA to examine the effect of traders’ demographic characteristics on factors contributing to food waste. The results showed that demographics factors, such as age, daily turnover, and market location, significantly influence procurement strategies. Key findings underscore the importance of proper packaging tailored to the specific type of vegetable and the need for supplier intervention, to ensure adequate packaging during delivery, thereby maintaining vegetable quality. Moreover, traders with higher turnover rates are advised to carefully manage their purchasing practices to minimize waste. These insights highlight the critical role of procurement strategies in reducing vegetable food waste and the need for targeted interventions across the supply chain.